Regulation of Economic Rights Protection for Women After Divorce From the Perspective of Maqasid Al-Syariah - Mugni, Mugni (Fakultas Syariah Institut Agama Islam Negeri Palu, 2025)
The purpose of this study is to explain the regulations on the protection of women's economic rights after divorce and to present a critique from the perspective of Maqasid al-Shari'ah on these regulations. This is a qualitative study, using a library research design. The data collection method employed is literature review. The results of the study indicate that the regulations on the protection of women's economic rights after divorce in Indonesia are contained in several legal provisions, such as Article 41 letter C of Law No. 1 of 1974 concerning Marriage, the Compilation of Islamic Law (KHI) Articles 149, 152, 158, 160, 97, 96, and Article 80 paragraph (4) letter (a), as well as Article 160 paragraph (4) of the KHI. In addition, it includes Supreme Court Regulation (PERMA) No. 3 of 2017, Supreme Court Circular Letters (SEMA) No. 1 of 2017, No. 3 of 2018, No. 2 of 2019, and No. 5 of 2021, the Decree No. 1669/DJA/HK.00/5/2021 on the Assurance of the Fulfillment of Women’s and Children’s Rights After Divorce, and the Circular Letter of the Directorate General of Religious Courts No. 1960/DjA/HK.00/6/2021. However, there are legal loopholes in these regulations regarding the protection of economic rights after divorce, making it uncertain and not fully guaranteed that women's economic rights will be fulfilled. Therefore, the regulations cannot entirely ensure the protection of women's economic rights after divorce. This is not in line with Hifz al-Din (protection of religion), as it contradicts the principles of economic rights for women after divorce as mandated by Islamic law. It also does not align with Hifz al-Nafs (protection of life), as it poses risks to the psychological and physical well-being of women, potentially endangering their lives. Furthermore, it is inconsistent with Hifz al-Mal (protection of wealth), as it may jeopardize the financial stability of women who are housewives, particularly those who are elderly or suffering from health issues.